2000
DOI: 10.1095/biolreprod63.4.1115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thyroid Hormone on Leydig Cell Regeneration in the Adult Rat Following Ethane Dimethane Sulphonate Treatment1

Abstract: We tested the effects of thyroid hormone on Leydig cell (LC) regeneration in the adult rat testis after ethane dimethyl sulphonate (EDS) treatment. Ninety-day-old, thyroid-intact (n = 96) and thyroidectomized (n = 5) male Sprague-Dawley rats were injected intraperitoneally (single injection) with EDS (75 mg/kg) to destroy LC. Thyroid-intact, EDS-treated rats were equally divided into three groups (n = 32 per group) and treated as follows: control (saline-injected), hypothyroid (provided 0.1% propyl thiouracil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 40 publications
(77 reference statements)
3
52
1
2
Order By: Relevance
“…Previous studies of adult Leydig cell differentiation, either during normal development or following EDS in the adult, have identified peritubular, spindleshaped/mesenchymal cells as the immediate precursor cells (Haider et al 1995, Russell et al 1995, Ariyaratne et al 2000a, 2000b. In addition, spindle-shaped peritubular cells have been described recently as Leydig cell stem cells (Ge et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of adult Leydig cell differentiation, either during normal development or following EDS in the adult, have identified peritubular, spindleshaped/mesenchymal cells as the immediate precursor cells (Haider et al 1995, Russell et al 1995, Ariyaratne et al 2000a, 2000b. In addition, spindle-shaped peritubular cells have been described recently as Leydig cell stem cells (Ge et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have indicated that Leydig cell precursor cells are predominantly peritubular, based on morphological and immunohistochemical evidence (Haider et al 1995, Russell et al 1995, Haider & Sevros 1998, Ariyaratne et al 2000a, 2000b. A recent study, however, has reported that the progenitor cells are vascular smooth muscle cells and pericytes, based on the apparent neuronal and glial properties of these cells (Davidoff et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Microscope images were captured on Spot analysis software (Diagnostic Instruments Inc., Sterling Heights, MI, USA) using a 3100 oil-free Figure 1 Diagram to illustrate the treatment and sampling regimen applied (small dots above the bar indicate approximate blood sampling times). The morphological changes during pubertal Leydig cell differentiation (after [16][17][18] ) are illustrated at their corresponding times in the upper section of the figure. GD, gestational day; PND, postnatal day; DBP, dibutyl phthalate; DES, diethylstilbestrol.…”
Section: Leydig Cell Countingmentioning
confidence: 99%
“…Leydig cells were recognized by their oval to spherical nucleus with a thin rim of heterochromatin and prominent nucleolus. [16][17][18] Finally, the entire testis cross-section was captured with 31.25 objective for determination of the surface area of each testis section. The total number of Leydig cells within the whole testis was estimated by the formula 19 : Nˆ5Q31/f 1 31/f 2 31/f 3 , where Nˆis the estimated total number, Q is the number of Leydig cells counted in the disector, f 1 is the fraction of tissue (i.e., number of randomly selected slices/number of total slices), f 2 is the fraction of sections (i.e., total number of randomly selected sections/number of total sections) and f 3 is the sampling fraction (i.e., S volume of dissectors/S volume of the entire testis section).…”
Section: Leydig Cell Countingmentioning
confidence: 99%
“…This regenerative process of LC involves differentiation of mesenchymal cells into new LC [22,27] and mitotic divisions of newly formed LC [22,27] similar to LC differentiation in the prepubertal rat testis. Despite the considerable body of information available on cellular changes during prepubertal development [1,17], only a few investigations have attempted to study the changes in testicular interstitium quantitatively following EDS treatment [4,15,32]. None of these studies have analyzed the kinetic changes that occur in all interstitial cell types in the testis during this repopulation process and the changes in the testicular steroidogenic function after EDS administration.…”
mentioning
confidence: 99%